Treatment of a glioblastoma multiforme dural metastasis with stereotactic radiosurgery: A case report and select review of the literature. (February 2018) - Hintenlang, Lauren L.; Miller, Daniel H.; Kaleem, Tasneem; Patel, Neema; May, Byron C.; Tzou, Katherine S.; Vallow, Laura A.; Buskirk, Steven J.; Miller, Robert C.; Ko, Stephen J.; Jaeckle, Kurt A.; Trifiletti, Daniel M.; et al.
Highlights: Glioblastoma multiforme accounts for approximately 75% of all high grade gliomas. Limited data exists regarding extracranial or intracranial GBM metastasis. We describe stereotactic radiosurgery (SRS) treatment of a GBM dural metastases. SRS may provide increased local control, and limit disease spread/symptomatology. Abstract: Glioblastoma multiforme (GBM) is a primary brain neoplasm accounting for approximately 75% of all high grade gliomas. It is diffusely infiltrative and exhibits rapid proliferation with a poor overall prognosis. Maximum surgical resection and postoperative radiotherapy, accompanied by concurrent and adjuvant temozolomide chemotherapy, remain the standard of care without major therapeutic advances over the past 10 years. Herein, we present the case of a 64-year-old Caucasian male with a GBM who subsequently developed a left frontal dural metastasis, subsequently treated with stereotactic radiosurgery (20 Gy in 1 fraction). With six month follow-up, the patient showed near complete resolution of his dural metastases and no overall change in neurological symptoms or side effects following radiosurgery. Due to the paucity of clinical literature regarding dural metastases from GBM, its optimal treatment remains unknown. While the role of SRS has yet to be defined in this setting, here we provide evidence suggesting its overall efficacy in the treatment of select dural GBM metastases.